Glutamic acid decarboxylase-IgG among T2DM patients with HCMV infection and HbA1c levels - Lajan Q Rahman; Saeed Kh Hussain; Pinar Kh Khudhur; Amin A Bakir (Diyala Journal of Medicine, 2018)
Background:Prophetic immune marker glutamic acid decarboxylase (GAD) autoantibody is a distinctive diagnosis between Type 1 Diabetes Mellitus and Type 2 Diabetes Mellitus. Individuals have diagnose as Latent Autoimmune Diabetes in adults (LADA) has such autoantibody, which those patients  incorrectly diagnosed as T2DM.